The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/fsn3.3037
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of fish oil containing Omega‐3 fatty acids and Lactobacillus plantarum on colorectal cancer

Abstract: Colorectal cancer (CRC) is one of the deadliest malignancies. Recent attempts have indicated the role of diet in the etiology of CRC. Natural dietary compounds such as probiotics and Omega‐3 fatty acids that act synergistically can be beneficial in finding a tremendous solution against CRC. To date, the combined effect of fish oil containing Omega‐3 fatty acids (Omega‐3) and Lactobacillus plantarum (L. plantarum) on CRC has been left behind. We here evaluated the effects of co‐encapsulation of Omega‐3 and prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…The results showed that P1 and P2 were resistant only to vancomycin and teicoplanin, trimethoprim-sulfamethoxazole, and tetracycline and sensitive to the others. Since probiotics and antibiotics are used simultaneously in the treatment of some infectious diseases, if the probiotics are not resistant, it is the first organism that is destroyed [ 30 ]. Lactobacilli, the main bacteria used as probiotics, therefore possess intrinsic resistance to some antibiotics, making them suitable for coadministration with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that P1 and P2 were resistant only to vancomycin and teicoplanin, trimethoprim-sulfamethoxazole, and tetracycline and sensitive to the others. Since probiotics and antibiotics are used simultaneously in the treatment of some infectious diseases, if the probiotics are not resistant, it is the first organism that is destroyed [ 30 ]. Lactobacilli, the main bacteria used as probiotics, therefore possess intrinsic resistance to some antibiotics, making them suitable for coadministration with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the culture medium in the wells was aspirated, and 50 μ L of dimethyl sulfoxide (DMSO) from Merck, Germany, was added to dissolve the formazan crystals. The results were measured by recording the absorbance at 540 nm using a microplate reader (BioTek Instruments, Inc., Vermont, USA) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…While in the present study, the C18:2n6 was natively present in milk, in the other studies it was directly added to the milk. The combined effect of Omega-3 and L. plantarum on the viability and apoptosis gene expression of cancer cells has been recently tested [22] in fermented milk.…”
Section: Discussionmentioning
confidence: 99%
“…The coadministration of probiotics with Omega-3 reduced liver fat, improved serum lipids and metabolic profile, and reduced the chronic systemic inflammatory state in type-2 diabetic patients [20,21]. The combined effect of Omega-3 and L. plantarum has been recently tested on the viability and apoptosis gene expression of cancer cells [22]. These studies have highlighted the role of fatty acids in influencing and regulating the growth of microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…GAPDH (housekeeping gene) expression level was used for normalization. Finally, the average of Double Ct values ​​was assayed to determine relative expression levels of BAX, BCL‐2, and Caspase‐3 (CASP‐3) apoptosis genes that were calculated using the comparative Ct method 16 …”
Section: Methodsmentioning
confidence: 99%